AUGMENTED REALITY AS A LEARNING FOR PROCESSING AND MARKETING WATER HYACINTH PRODUCTS IN PERUM JASA TIRTA II WITH PRISM METHOD - Ika Putri Puspitasari; Deden Witarsyah (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
Perum Jasa Tirta II (PJT II) has launched the